Verbalisation of feelings and emotions through the description of nature in Saken Zhunusov’s «The Path» (Amanai men Zamanai) - Abdrakhmanova Ж.Б.; Amalbekova М.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
Emotiology has acquired the status of one of the priority areas of traditional linguistics in recent decades. The mastery of the means of expressing emotions and the ability of the author of a work to convey implicit emotive meanings that can be reflected in the content through grammatical and lexical units play a determining role in the formation of semantic and communicative context. The article analyses the stylistic techniques and lexical means used in verbalization of feelings and emotions of the heroes of Saken Zhunusov’s work “The Path”. The relationship between the emotional state of a person and the description of natural phenomena is revealed. In the process of the analysis it is established that verbalization of feelings and emotions of heroes occurs with the use of lexical units with emotional colouring, metaphorisation, repetition and colour solution. The landscape sketches in the work are characterised by the prevalence of negative emotions because of the central theme of the work – collectivisation in Kazakhstan in the 1930s.